Akuntabilitas dalam Hubungan Keagenan dan Filosofi Tri Hita Karana - Dewi, Ni Wayan Yulianita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2007)
The accountability of principal-agent relationship between the company owner (principal) and management (agent) only reflects the relationship between hu¬mans. In the practice, relationship between individuals involved in the principal- agent relationship often experiences disharmony caused by opportunistic attitude of a Party (agent) as the manifestation of egoistic, materialistic, and utilitarian characters. Agents as human equip with opportunistic behavior, forcing them to underline self-interest, precisely to act with personal welfare interest, not for prin¬cipal wealth interest. Such phenomenon requires the injection of principal-agent relationship values to create more harmonic relationship and collective welfare. A base used in the injec¬tion of this value may be the life philosophy attended by Balinese, likes tri hita karana philosophy. Tri hita karana philosophy asserts that the collective welfare surfaces if the human experiences harmonic relationship with God, with other humans and with nature. Harmonic relationship between human and God appears within the behavior re¬flecting the divine awareness. Harmonic relationship between human and other human reflects in the behavior of respecting other interest, creating the peace and harmony with internal and external parties of the company. Harmonic rela¬tionship between human and nature develops through the maintenance and the conservation of natural substances. Harmonic relationship between human and God, human and other humans, and human and nature, in the principal-agent relationship should be minimize the interest conflict to produce a material or im¬material welfare for all. Keywords: accountability, principal-agent relationship, tri hita karana philoso¬phy The accountability of principal-agent relationship between the company owner (principal) and management (agent) only reflects the relationship between humans. In the practice, relationship between individuals involved in the principal- agent relationship often experiences disharmony caused by opportunistic attitude of a Party (agent) as the manifestation of egoistic, materialistic, and utilitarian characters. Agents as human equip with opportunistic behavior, forcing them to underline self-interest, precisely to act with personal welfare interest, not for principal wealth interest. Such phenomenon requires the injection of principal-agent relationship values to create more harmonic relationship and collective welfare. A base used in the injection of this value may be the life philosophy attended by Balinese, likes tri hita karana philosophy. Tri hita karana philosophy asserts that the collective welfare surfaces if the human experiences harmonic relationship with God, with other humans and with nature. Harmonic relationship between human and God appears within the behavior reflecting the divine awareness. Harmonic relationship between human and other human reflects in the behavior of respecting other interest, creating the peace and harmony with internal and external parties of the company. Harmonic relationship between human and nature develops through the maintenance and the conservation of natural substances. Harmonic relationship between human and God, human and other humans, and human and nature, in the principal-agent relationship should be minimize the interest conflict to produce a material or immaterial welfare for all. Keywords: accountability, principal-agent relationship, tri hita karana philosophy